Seattle's Bicycle Stations: A Social and Infrastructure Support Network for Tired, Wet, and Caffeine Deprived Cyclists - Kovacs, Victoria Laurel (My University, 2014)
Globally, bicycling is becoming a major means of transportation for its adaptability, affordability, and convenience. However, as compared with other developed nations, the US lags behind in conventional bicycle use, due to automobile driven policies. As cities continue to grow, there is a demand for dense, urban environments which support walkable lifestyles. Bicycling is well suited to high density living, and can improve the quality of life in cities by reducing air pollution, improving community health, and enabling social equity. Seattle is a progressive city in the US that has advocated for the implementation of a new bicycle network for riders of all ages and abilities. Moreover, at the city, state, and national level, increased bicycle ridership has become a transportation priority. This thesis proposes a network of bicycle stations throughout Seattle to encourage ridership, and add safety and convenience for cyclists, and signify bicycling is a normal, everyday activity.
Thesis (Master's)--University of Washington, 2013
Keywords: Architecture; Bicycle; Planning; Seattle; Urban Design; Architecture; architecture